A proposed framework for managing service parts in automotive and aerospace industries - de Souza, R.; Tan, Albert; Othman, H.; Garg, M. (Emerald Group Publishing, 2011)
Purpose: The purpose of this paper is to study the process, network, skills and practices of service parts logistics organizations in the Asia Pacific region. Specifically, it attempts to propose a new framework for service parts logistics management based on interview inputs from several leading automotive and aerospace companies. This paper also seeks to identify the trends and opportunities for service parts logistics in Singapore. Design/methodology/approach: Companies from aerospace and automotive industries involved in service logistics activities were involved in the study. Data were obtained primarily through interviews with key executives of the company. Findings: This paper summarizes some of the industry findings on service parts logistics in the Asia Pacific region. To succeed in the service logistics business, companies should not focus on cost factors alone. Instead, companies should adopt the proposed framework and look into other factors. Research limitations/implications: The research is limited to companies in the aerospace and automotive industries only. Practical implications: This framework was drawn from industry inputs and can be easily applied in decision making. Originality/value: The paper provides a new framework to assist decision makers in deciding where a company should locate its service part logistics hub.